Prenatal risk stratification of severe small-for-gestational-age infants: a Japanese multicenter study. (17th April 2016) - Yoshida, Aya; Umehara, Nagayoshi; Sasahara, Jun; Ozawa, Katsusuke; Ichizuka, Kiyotake; Tanaka, Kei; Tanemoto, Tomohiro; Ishikawa, Hiroshi; Murakoshi, Takeshi; Kiyoshi, Kenji; Oba, Mari S.; Ishii, Keisuke; et al.
Abstract: Objective : To establish a prenatal prognostic classification of severe small-for-gestational-age (SGA) infants based on gestational age and fetal findings. Methods : A retrospective cohort study of 366 singleton infants (birth weight <3rd percentile) delivered between 22 and 34 weeks' gestation at nine tertiary perinatal centers. A decision tree model was developed for the prediction of death or severe morbidity. Results : There were 35 infants with poor outcome. Prematurity was the most powerful factor in those born before 27.9 weeks' gestation, while oligohydramnios was the most powerful factor in those born at 27.9 weeks or after. The rate of poor outcome in infants born before 25.1 weeks, between 25.1 and 27.9 weeks, at 27.9 weeks or after with oligohydramnios, at 27.9 weeks or after without oligohydramnios, was 53.9%, 18.2%, 13.6% and 3.2%, respectively. Conclusions : Risk stratification based on gestation of 25 weeks, 28 weeks and oligohydramnios may aid in prognosis of severe SGA infants.